Regulacja środkowego odcinka cieku Zielonka w Parku Leśnym Arkońskim w Szczecinie = Regulation of de middle section of the stream Zielonka in Park Leśny Arkoński in Szczecin - Wira, Jerzy; Kwieciński, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This text described problems conected with environmental protection of local nature of Park Leśny Arkoński. Presented problems are naturegenic and anthropogenic. That was cased by storms in june and july 97. Big rains and very closed standing buildings were reasons of reinforcing this phenomenon. Local dry tank builded closed to Las Arkoński Park will bepossibility for lowering of extremal flows in consequention il will lowering costs of exploatation forest warters streaming in Las Arkoński Park.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)